Exploring monkeypox virus proteins and rapid detection techniques - Sagdat, Kamila; Batyrkhan, Assel; Kanayeva, Damira (Frontiers in Cellular and Infection Microbiology, 2024)
Monkeypox (mpox) is an infectious disease caused by the mpox virus and can potentially lead to fatal outcomes. It resembles infections caused by viruses from other families, challenging identification. The pathogenesis, transmission, and clinical manifestations of mpox and other Orthopoxvirus species are similar due to their closely related genetic material. This review provides a comprehensive discussion of the roles of various proteins, including extracellular enveloped virus (EEV), intracellular mature virus (IMV), and profilin-like proteins of mpox. It also highlights recent diagnostic techniques based on these proteins to detect this infection rapidly.